Pengaruh Sistem Pengendalian Internal, Akuntabilitas, Dan Transparansi Terhadap Pencegahan Kecurangan Pengelolaan Dana BOS: (Studi Kasus Pada Seluruh SMA dan SMK di Kabupaten Klungkung) - Dewi, Ni Kadek Mayang Sari; Putra, I Putu Deddy Samtika (UNHI Press, 2025)
Fraud prevention is reducing or eliminating the chances or avenues for committing fraud through the implementation of risk management strategies, particularly focusing on fraud risk management, internal controls, and transparent corporate governance. This research aims to determine the influence of the Internal Control System, Accountability and Transparency on the Prevention of Fraud in the Management of BOS Funds (Case Study of All High Schools and Vocational Schools in Klungkung Regency). The population were all school principals, school BOS treasurers and school committee treasurers in all high schools and vocational schools in Klungkung Regency with a total of 54 respondents. Sample in this study was 54 respondents using the Saturated Sample method and tested using multiple linear regression analysis techniques. The results indicate that individualy, the Internal Control System, Accountability, and Transparency has a positive and significant effect on preventing fraud in the management of BOS funds. Looking at the research results, all parties who need data, including parents/guardians of students, will receive the same information as the school regarding the management of BOS funds so that the more transparent the school is in managing BOS funds, the potential for preventing fraud in the school will increase.